Identification of small molecule inhibitors of penicillin-binding protein 2a of methicillin-resistant Staphylococcus aureus for the therapeutics of bacterial infection: Inhibitors of PBP2a of methicillin-resistant S. aureus - Anwer, Razique (Cellular and Molecular Biology, 2024)
The penicillin binding protein 2a (PBP2a) is a key enzyme associated with bacterial cell wall synthesis and bacterial infection. Therefore, targeting PBPa2 offers a promising approach for the therapeutics of bacterial resistance and infection. This study presents a comprehensive analysis of alpha-mangostin as a potential inhibitor of PBPa2. Molecular docking simulations revealed a strong binding affinity between alpha-mangostin and PBP2a, with an affinity score of -6.01 kcal/mol. Notably, alpha-mangostin formed a preferential hydrogen bond with THR216 of PBP2a, alongside several other polar and hydrophobic interactions. ADME and Toxicity predictions indicated that alpha-mangostin possesses favourable pharmacokinetic properties, suggesting its potential as a therapeutic agent. PASS analysis further highlighted its broad range of favourable biological properties. SwissTargetPrediction analysis reinforced these findings, indicating alpha-mangostin's association with various biological processes. Cell toxicity assays demonstrated that alpha-mangostin had no significant impact on the viability of HEK-293 cells, suggesting its potential safety for further development. The IC50 value for alpha-mangostin was found to be 33.43µM. Fluorescence-based binding assays showed that alpha-mangostin effectively inhibited PBP2a activity in a concentration-dependent manner, supporting its role as an inhibitor. In conclusion, the results suggest alpha-mangostin as a promising candidate for inhibiting PBP2a. Further, extensive studies are warranted to explore its clinical applications.